Improved Synthesis of Asymmetric Curcuminoids and Their Assessment as Antioxidants - Yang-Je Cheng; Cai-Wei Li; Cing-Ling Kuo; Tzenge-Lien Shih; Jih-Jung Chen (Molecules, 2022)
In this paper, the syntheses of twelve asymmetric curcumin analogs using Pabon’s method are reported. Generally, the previously reported yields of asymmetric curcuminoids, such as 9a (53%), 9c (38%), and 9k (38%), have been moderate or low. Herein, we propose that the low yields were due to the presence of water and n-BuNH2 in the reaction media. To prove this formulated hypothesis, we have demonstrated that the yields can be improved by adding molecular sieves (MS) (4 Å) to the reaction mixture, thus reducing the interference of water. Therefore, improved yields (41–76%) were obtained, except for 9b (36.7%), 9g (34%), and 9l (39.5%). Furthermore, compounds 9b, 9d, 9e, 9f, 9g, 9h, 9i, 9j, and 9l are reported herein for the first time. The structures of these synthetic compounds were determined by spectroscopic and mass spectrometry analyses. The free radical scavenging ability of these synthetic asymmetric curcuminoids was evaluated and compared to that of the positive control butylated hydroxytoluene (BHT). Among the synthesized asymmetric curcuminoids, compounds 9a (IC50 = 37.57 ± 0.89 μM) and 9e (IC50 = 37.17 ± 1.76 μM) possessed effective 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging abilities, and compounds 9h (IC50 = 11.36 ± 0.65 μM) and 9i (IC50 = 10.91 ± 0.77 μM) displayed potent 2,2’-azinobis-(3-ethylbenzthiazoline-6-sulphonate) (ABTS) radical scavenging abilities comparable to that of curcumin (IC50 = 10.14 ± 1.04 μM). Furthermore, all the synthetic asymmetric curcuminoids were more active than BHT.